Knowledge Production in the Arts: History, Concept and Methodological Considerations * - Nelund, Sidsel (Peripeti, 2021)
Since the 1990s, the term knowledge production has been used to designate a set of artistic practices mainly within what would be termed critical art and theory, especially in a European and North American context. This article follows the concept of knowledge production from its inception in the twentieth century’s neoliberal economy into visual arts and practices of artistic, curatorial, and educational research. Recognizing that the term is applied in a widespread, divergent manner, the article proposes a definition of a methodological approach to studies of knowledge production in arts based on actual case studies. It also develops a thorough theorization of the workings of the concept of knowledge production as an apparatus.